PENGARUH KEPEMIMPIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) AMANAH UMMAH LEUWILIANG BOGOR - Suci Yunita Pratiwi (Jurnal Menara, 2024)
The purpose of this research is to determine the influence of leadership and motivation on employee performance at PT. Sharia People's Empowerment Bank (BPRS) Amanah Ummah Pusat Leuwiliang Bogor. Research is associative with a quantitative approach. The sample used in this research was 66 respondents. Data collection techniques by distributing questionnaires, and data analysis techniques using validity testing, reliability of classical assumption tests, simple linear analysis, multiple regression analysis, correlation coefficient, coefficient of determination, hypothesis testing, F test and T hitung test. The results of the research are that together there is an influence between work leadership and motivation on employee performance at PT. BPRS (Sharia People's Financing Bank) Amanah Ummah Pusat Leuwiliang Bogor. This can be proven from the multiple linear regression equation, namely Y = 8.867 + 1.001 Thus the decision taken by Ho is rejected and Ha is accepted. This means that work leadership and motivation variables are able to influence employee performance variables. The coefficient of determination or R square value is 0.854 or 85.4%. The dependent variable is employee performance (Y), the variation of which can be explained by the variables work leadership (X1) and motivation (X2) and the remaining 14.6% is explained outside the variables used